Genome-Wide Association Study Provides Insight into the Genetic Control of Plant Height in Rapeseed (Brassica napus L.) - Sun, Chengming; Wang, Benqi; Yan, Lei; Hu, Kaining; Liu, Sheng; Zhou, Yongming; Guan, Chunyun; Zhang, Zhenqian; Li, Jiana; Zhang, Jiefu; Chen, Song; Wen, Jing; et al. (Frontiers in Plant Science, 2016)
Plant height is a key morphological trait of rapeseed. In this study, we measured plant height of a rapeseed population across six environments. This population contains 476 inbred lines representing the major Chinese rapeseed genepool and 44 lines from other countries. The 60K Brassica Infinium® SNP array was utilized to genotype the association panel. A genome-wide association study (GWAS) was performed via three methods, including a robust, novel, nonparametric Anderson-Darling (A-D) test. Consequently, 68 loci were identified as significantly associated with plant height (P < 5.22 × 10-5), and more than 70% of the loci (48) overlapped the confidence intervals of reported QTLs from nine mapping populations. Moreover, 24 GWAS loci were detected with selective sweep signals, which reflected the signatures of historical semi-dwarf breeding. In the linkage disequilibrium (LD) decay range up- and downstream of 65 loci (r2 > 0.1), we found plausible candidates orthologous to the documented Arabidopsis genes involved in height regulation. One significant association found by GWAS colocalized with the established height locus BnRGA in rapeseed. Our results provide insights into the genetic basis of plant height in rapeseed and may facilitate marker-based breeding.